ABRI masuk desa Kodam III Siliwangi: Program pembangunan desa masa Orde Baru (1980-1998) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This study aims to determine the development of the ABRI Entering Village (AMD) program from the beginning until the end of the New Order system in 1980-1998. This study uses a historical research method, with four important steps, namely heuristics, criticism, interpretation, and historiography. The research sources were collected from several sources, including the Library of the Indonesian Education University (UPI), the Batoe Api Jatinangor Library, the National Library of the Republic of Indonesia, the Central Library of the Army History Service, and the Indramayu Regency Library. The results of of this study: 1) the AMD program was motivated by internal factors namely domestic sociopolitical conditions as a result of the 1965 G30S incident, and external factors namely the development of communism ideology in the world; 2) the AMD program has been implemented successfully so that there is a currently sustainable development program with the same theme called the Manunggal Army to Build Villages (TMMD); 3) the AMD program has had a positive impact on the community, such as reviving the spirit of mutual cooperation and the community’s sense of trust in ABRI.
Keywords: ABRI; New Order; village development